2009
DOI: 10.1080/17470910802176326
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of temporally distinct responses to emotional facial expressions

Abstract: Understanding the temporal dynamics of brain function contributes to models of learning and memory as well as the processing of emotions and habituation. In this article, we present a novel analysis technique to investigate spatiotemporal patterns of activation in response to blocked presentations of emotional stimuli. We modeled three temporal response functions (TRFs), which were maximally sensitive to the onset, early or sustained temporal component of a given block type. This analysis technique was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
5
3
0
Order By: Relevance
“…It has been suggested that these inconsistencies likely reflect methodological differences in the temporal parameters as the studies varied in the length of blocks and experimental runs. It has been proposed that the amygdala does not exhibit habituation when shorter (e.g., 18 s) blocks are used (Haas et al, 2008 ), which is consistent with our data and design (one block lasted 20 s).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that these inconsistencies likely reflect methodological differences in the temporal parameters as the studies varied in the length of blocks and experimental runs. It has been proposed that the amygdala does not exhibit habituation when shorter (e.g., 18 s) blocks are used (Haas et al, 2008 ), which is consistent with our data and design (one block lasted 20 s).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings differ from previously reported data (Phillips et al, 2001 ; Fischer et al, 2003 ; Williams et al, 2004 ) as we did not observe a rapid habituation of the amygdala to repeatedly presented emotional stimuli thereby disproving the idea that the signal decrease could be attributed to habituation. Supporting our results, a recent study (Haas et al, 2008 ) also failed to find any evidence for amygdala habituation. It has been suggested that these inconsistencies likely reflect methodological differences in the temporal parameters as the studies varied in the length of blocks and experimental runs.…”
Section: Discussionsupporting
confidence: 90%
“…This is not inconsistent with the observation in a recent meta-analysis that amygdala activity was significantly greater for explicit (attended) fear perception vs. implicit fear perception [34]. In addition, the finding that amygdala demonstrates a distinct temporal profile from other structures during emotional face processing could also explain why more functional connections with amygdala were not observed in the current analysis [10]. Instead, the structure which contributed the most in discriminating between the fear and neutral conditions was thalamus (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…This mixed block/event-related design was chosen to allow the BOLD signal to return to baseline between images, which increases functional signal-to-noise ratio, statistical power, and robustness of the results (Amaro and Barker, 2006). The duration of each block was short enough to prevent habituation in the amygdala (Haas et al, 2009). To prevent unintentional influences on the study participants, which may have confounded our results, the experimenters (GD and ELS) were blinded with respect to subjects' group assignment until after the end of the post-intervention fMRI experiment.…”
Section: Stop Stressingmentioning
confidence: 99%